Cultural and Traditional Relations in Madura Regarding Gender Equality in the Practice of Marriage Guardianship - Umi, Umi Supraptiningsih; Rahmawati, Theadora Rahmawati; Makhrus, M. Makhrus Fauzi; Mubarok, Faidol Mubarok (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2024)
Problem statement: Marriage guardianship is a significant aspect of Islamic marriage, wherein the guardian assumes responsibility for the marriage of a female. The influence of culture and tradition in the practice of marriage guardianship in Madura frequently leads to challenges related to the selection of a male bride. Objective: This study aims to analyse the relationship between Madurese culture and traditions and gender equality in the practice of marriage guardianship. Methods: This research employs a qualitative approach, utilising data collection techniques such as participatory observation, in-depth interviews, and the analysis of documents pertinent to Madurese culture and traditions. The collected data is subsequently analysed using content analysis to ascertain the impact of Madurese culture and traditions on gender equality within the context of marriage guardianship. Results: This study reveals a shift and transformation in gender awareness in Madura, driven by efforts from community groups and non-governmental organisations to promote gender equality in marriage brokerage practices. Nevertheless, these initiatives continue to encounter formidable cultural and traditional obstacles. The relationship between Madura's culture and traditions and gender equality in marriage brokerage practices remains significant. Conclusion: Comprehensive and integrated efforts are essential from various stakeholders, including the community, government, and non-governmental organisations, to foster more inclusive gender awareness and facilitate positive changes in marriage brokerage practices in Madura.